The Screaming Heath: Dark Ecology and the Collapse of Anthropocentrism in Shakespeare’s King Lear - Julianti Hairani; Purwarno Purwarno (Hasanuddin University, 2026)
This study demonstrates that King Lear can be read as an ecological tragedy in which human authority is destabilized through the interaction of dark ecological forces and Foucauldian power structures. By applying Timothy Morton’s concept of dark ecology and Michel Foucault’s theory of discourse, this research reveals that nature in the play was not merely symbolic but actively participates in the collapse of anthropocentrism. This article was a descriptive-qualitative study using a literature review method, with reference to several supporting sources throughout the research process. The primary data used here are narrative scripts from Shakespeare's King Lear drama series and events that explicitly mention nature as a significant narrative device and setting. This research showed that dark ecology functioned as a form of deconstruction of human identity in King Lear. From Michel Foucault’s perspective, anthropocentric authority couldn’t fully dominate ecological reality, as identity itself was produced through social systems and relations of power. Consequently, when those systems collapse, human identity also became unstable and fragmented. In line with this view, Timothy Morton argues that the collapse of anthropocentrism in King Lear signals the loss of humanity’s position as the sole center of knowledge and meaning within the world.